2020
DOI: 10.1007/s10067-020-04951-6
|View full text |Cite
|
Sign up to set email alerts
|

Lung function is associated with minimal EQ-5D changes over time in patients with systemic sclerosis

Abstract: In systemic sclerosis (SSc) therapeutic efforts are often directed to prevent progressive respiratory impairment, but it is unclear to what extent changes in pulmonary function tests (PFTs) are associated with health-related quality of life (HRQoL). The aim of our study is to evaluate how modifications in PFTs contribute to longitudinal variations in HRQoL, assessed through the multidimensional questionnaire EQ-5D, in patients with SSc. We included SSc patients with forced vital capacity (FVC%), diffusing capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…30 In our study, the EQ-5D-5L score increased significantly by 0.03 for 10% increase of the FVC. This finding is consistent with that of Ciaffi et al, 31 who had performed a retrospective study in 378 patients with SSc including 156 patients with ILD and pulmonary arterial hypertension. They reported that changes in lung function have a significant impact on HRQoL using the EQ-5D score in both its utility score (p = 0.003) and VAS (p < 0.001) over time.…”
Section: Discussionsupporting
confidence: 92%
“…30 In our study, the EQ-5D-5L score increased significantly by 0.03 for 10% increase of the FVC. This finding is consistent with that of Ciaffi et al, 31 who had performed a retrospective study in 378 patients with SSc including 156 patients with ILD and pulmonary arterial hypertension. They reported that changes in lung function have a significant impact on HRQoL using the EQ-5D score in both its utility score (p = 0.003) and VAS (p < 0.001) over time.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with earlier literature, our study shows that a history of smoking is associated with a lower prevalence of ATA 10 23 and we confirm that this imbalance is found typically in female patients. 24 Additionally, we notice that this association is dose-dependent (ie, the higher the exposure rate, the lower the chance to be ATApositive), which underlines the hypothesis that, indeed, exposure to cigarette smoke might impact the ATAspecific B cell responses. This finding is unexpected if we consider what happens in other autoimmune diseases such as RA or systemic lupus erythematosus (SLE).…”
Section: Systemic Sclerosis Systemic Sclerosis Systemic Sclerosismentioning
confidence: 54%
“…10 23 In an analysis of the autoantibody profile of 361 patients of the Leiden Combined Care in SSc cohort, we reported the same finding, but we also showed that smoking might have different effects on autoantibodies in men and women, with never-smoking women being more frequently ATApositive than ever-smoking women. 24 In rheumatoid arthritis (RA), smoking has a wellestablished impact on disease susceptibility and confers a risk for the development of anti-citrullinated peptide antibodies (ACPA) and rheumatoid factor, in particular in patients carrying specific HLA-DRB1 variants. 25 These observations have fuelled the hypothesis that, in a susceptible individual, chronic exposure to specific antigens, for example, in the lungs, can trigger a targeted chronic autoimmune response.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…Separate case studies from Italy confirmed a higher frequency of silicone breast implants [13] and a higher risk for rupture [14] specifically in patients with ARA-positive SSc. Although smoking has been identified as a potential trigger for autoimmunity in general [15], and a risk factor for worse prognosis in patients with SSc [16], ATA were found to be negatively associated with smoking (OR 1.77, 95% CI 1.04-2.99, P ¼ 0.034) [17]. This is an unexpected finding of a detrimental environmental factor acting as a protective influence against developing specific autoantibodies in SSc and merits further evaluation.…”
Section: Infectious Agents/pathogensmentioning
confidence: 77%